Pacem In Terris dalam Kebijakan Luar Negeri Tahta Suci Vatikan terhadap Konflik Suriah - Nadya Yolanda Nainggolan; Mohamad Rosyidin; Muhammad Faizal Alfian (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
Syrian conflict was one of the effects of the Arab Spring and has been evolving into a proxy war and get prolonged. Among many actors who are active and has their own interest in the international politics, the Holy See came to fight for peace in Syria. This study aimed to explain the reason why the Holy See was getting involved in pursuing peace in Syria. This research used a desk research method with an explanative type. This study used the theory of constructivist norms and the concept of foreign policy. Constructivism assumed that norms, one of which is domestic norms adopted by a country, can influence the interests of a country and affect the foreign policy. In this case, Pacem In Terris, as one of the encyclicals in Catholic social teaching, has become one of the domestic norms of the Holy See. Therefore, this study found out that Pacem In Terris was the domestic norm of the Holy See affected the interests of the Holy See to fight for peace in peaceful ways and then as a 'map' that influenced the policy of the Holy See to participated through several foreign policies towards Syria.